ORFeome Phage Display Reveals a Major Immunogenic Epitope on the S2 Subdomain of SARS-CoV-2 Spike Protein - Rico Ballmann; Sven-Kevin Hotop; Federico Bertoglio; Stephan Steinke; Philip Alexander Heine; M. Zeeshan Chaudhry; Dieter Jahn; Boas Pucker; Fausto Baldanti; Antonio Piralla; Maren Schubert; Luka Čičin-Šain; et al. (Viruses, 2022)
The development of antibody therapies against SARS-CoV-2 remains a challenging task during the ongoing COVID-19 pandemic. All approved therapeutic antibodies are directed against the receptor binding domain (RBD) of the spike, and therefore lose neutralization efficacy against emerging SARS-CoV-2 variants, which frequently mutate in the RBD region. Previously, phage display has been used to identify epitopes of antibody responses against several diseases. Such epitopes have been applied to design vaccines or neutralize antibodies. Here, we constructed an ORFeome phage display library for the SARS-CoV-2 genome. Open reading frames (ORFs) representing the SARS-CoV-2 genome were displayed on the surface of phage particles in order to identify enriched immunogenic epitopes from COVID-19 patients. Library quality was assessed by both NGS and epitope mapping of a monoclonal antibody with a known binding site. The most prominent epitope captured represented parts of the fusion peptide (FP) of the spike. It is associated with the cell entry mechanism of SARS-CoV-2 into the host cell; the serine protease TMPRSS2 cleaves the spike within this sequence. Blocking this mechanism could be a potential target for non-RBD binding therapeutic anti-SARS-CoV-2 antibodies. As mutations within the FP amino acid sequence have been rather rare among SARS-CoV-2 variants so far, this may provide an advantage in the fight against future virus variants.